Multifidus Thickness Comparison between the Effectiveness of Abdominal Bracing and Maximum Expiration Maneuvers in Lumbo-Pelvic Upright Sitting Posture - Ko, Minjoo; Kim, Sujung (Journal of International Academy of Physical Therapy Research, 2020)
Background: Trunk flexor-extensor muscles’ co-activation and upright posture are important for spinal stability. Abdominal bracing and maximal expiration are being used as exercises to excel torso co-contraction. However, no study has on comparison of the effect of this exercise on multifidus in the upright sitting posture. Objectives: This study aims to verify the effectiveness of abdominal bracing and expiration maneuvers in lumbo-pelvic upright sitting. Design: Cross-sectional study. Methods: Eighteen healthy women were recruited for this study. The multifidus muscle thickness of all subjects was measured in three sitting conditions (lumbo-pelvic upright sitting, lumbo-pelvic upright sitting with abdominal bracing, and lumbo-pelvic upright sitting with maximum expiration) using ultrasound. One-way repeated measure analysis of variance was used for the evaluation. Results: Compared to lumbo-pelvic upright sitting, lumbo-pelvic upright sitting with abdominal bracing and lumbo-pelvic upright sitting with maximum expiration were associated with significantly increment of muscle thickness. There was no significant difference in muscle thickness between lumbo-pelvic upright sitting with abdominal bracing and lumbo-pelvic upright sitting with maximum expiration. Conclusion: Abdominal bracing and maximum expiration could be beneficial to increasing lumbar multifidus thickness in lumbo-pelvic upright sitting. KCI Citation Count: 0